2021
DOI: 10.15766/mep_2374-8265.11095
|View full text |Cite
|
Sign up to set email alerts
|

Introduction to Pain Management for Third-Year Medical Students Team-Based Learning Module

Abstract: Introduction: A frequently encountered complaint in primary care, pain has a variety of causes and treatments. To reduce mortality, the Centers for Disease Control released guidelines on opioid prescribing in 2016. Taking those guidelines into account, this team-based learning (TBL) module for third-year medical students on their family medicine clinical clerkship serves as an introductory application for treatment of nociceptive and neuropathic pain. Methods: Students accessed preparticipation reading materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Two studies [ 72 , 73 ] reported higher scores in tRAT compared to iRAT as their only knowledge results.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies [ 72 , 73 ] reported higher scores in tRAT compared to iRAT as their only knowledge results.…”
Section: Resultsmentioning
confidence: 99%
“… 11 Current UME-targeted publications emphasize pain management in palliative care 12 and family medicine. 13 These interventions highlight pain assessment and management specific to critically ill or dying patients and patients managing chronic pain, without focusing on assessment of acute pain in the undifferentiated patient. While MedEdPORTAL provides a handful of pain-related emergency medicine (EM) interventions, existing pieces are typically simulations or case-based learning scenarios utilizing a singular diagnosis (e.g., neck pain) as opposed to generalized acute pain.…”
Section: Introductionmentioning
confidence: 99%